MANUFACTURE OF X-RAY APPARATUS IN SERBIA - Misic, Miroslav; Stajic, Sava; Petrovic, Marko; Petrovic, Vladimir (HEALTH CARE, 2021)
X-ray diagnostics has an irreplaceable place in radiology despite other modern diagnostic methods. That is why the production of modern X-ray machines is strategically important for every health system. Serbia has a tradition of over 70 years in the production of X-ray machines. From the first device manufactured in Serbia in 1953, it kept pace with the world in technical and technological terms. X-ray machines were produced by the state company Jugorendgen from Nis. Unfortunately, the company Jugorendgen stopped production before it managed to make a digital X-ray machine. For the past 17 years, these devices have been manufactured by Visaris. Visaris is a private company from Belgrade, which has been developing and manufacturing digital X-ray machines and software systems since 2003. Its importance came to the forefront during the pandemic SARS-CoV-2 infection when the health system of Serbia needed more stationary and mobile X-ray machines in a short time period.
Keywords: X – ray machine, production, health system